Psychosocial Perspectives and the Issue of Prevention in Childhood Obesity - Stein, Daniel; Weinberger-Litman, Sarah L.; Latzer, Yael (Frontiers in Public Health, 2014)
A dramatic increase in childhood overweight/obesity has been recognized globally over the past 50 years. This observed increase may reflect genetic, as well as psychological, environmental, and socio-cultural influences. In the first part of this review we present an updated summary of the psychosocial factors associated with this change and discuss possible ways in which they operate. Among these factors , lower socio economic status (in both industrialized and non-industrialized countries), being female, belonging to a minority group, and being exposed to adverse life events may all be associated with a greater risk of childhood overweight/obesity. These influences may be mediated via a variety of mechanisms, in particular above average food intake of low nutritional quality, and reduction in physical activity. Other important psychosocial mediators include the influence of the family and peer environment, and exposure to the media. In the second part of the review we discuss the potential of psychosocial prevention programs to intervene in the processes involved in the rise of childhood overweight/obesity. Two points are emphasized. Firstly, prevention programs should be multidisciplinary, combining the knowledge of experts from different professions, and taking into consideration the important role of the family environment and relevant influential social organizations, particularly school. Secondly, effective change is unlikely to occur without large-scale programs carried out on a public policy level.